2009
DOI: 10.1590/s1982-56762009000600009
|View full text |Cite
|
Sign up to set email alerts
|

Ineficiência do silício no controle da ferrugem do cafeeiro em solução nutritiva

Abstract: Parte da Tese de Doutorado da primeira autora. Universidade Federal de Viçosa. Viçosa MG. 2008. RESUMOA ferrugem, causada por Hemileia vastatrix, é a principal doença do cafeeiro. Este trabalho avaliou o efeito do silício (Si) em alguns componentes de resistência do cafeeiro à ferrugem e o possível aumento na atividade de quitinases (QUI), β-1,3-glucanases (GLU) e peroxidases (POX). Mudas de cafeeiro (cv. Catuaí vermelho 44) foram crescidas em solução nutritiva de Clarck modificada, aerada, contendo 0 (-Si) ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…Coffee plants cannot uptake Si from roots and accumulate it in the shoots (Carré‐Missio et al , ) with great efficiency as compared to rice (Rodrigues et al , ). Coffee plants also show very low leaf Si absorption efficiency, mainly due to the quick polymerisation of PS on the leaf surface before uptake can occur (Carré‐Missio et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Coffee plants cannot uptake Si from roots and accumulate it in the shoots (Carré‐Missio et al , ) with great efficiency as compared to rice (Rodrigues et al , ). Coffee plants also show very low leaf Si absorption efficiency, mainly due to the quick polymerisation of PS on the leaf surface before uptake can occur (Carré‐Missio et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Não houve aumento na atividade dessas enzimas em folhas de plantas que receberam aplicação foliar de Si e a redução na severidade do oídio foi atribuída à barreira física formada pela polimerização do silicato e também ao efeito osmótico (Liang et al, 2005). Carré-Missio et al (2009a) observaram que plantas de cafeeiro (cv. Catuaí 44) crescidas em solução nutritiva contendo Si não apresentaram aumento no período de incubação e no período latente da ferrugem e nem mesmo redução no número de pústulas por folha, área pustular, expansão de pústulas e área abaixo da curva do progresso da ferrugem ou aumento na atividade de quitinases, β-1,3-glucanases e peroxidases.…”
unclassified
“…the product and was thus not efficiently translocated to the shoots. According to Carré-Missio et al (2009), coffee plants have been shown to be inefficient in uptaking Si from the nutrient solution and translocating it to the shoot because it was exclusively restricted to the roots, and no increase in resistance to rust was obtained. Conversely, for a Si-accumulator plant species, Resende et al (2013) observed that the area under anthracnose progress curve was reduced by 40% with the amendment of Si-deficient soil with calcium silicate.…”
Section: Resultsmentioning
confidence: 99%